Proximity and creation of relational value: Case of the automotive subcontracting of level two’s relationships in Morocco - El Kandili, Mohamed (Archives of Business Research, 2018)
The challenge which represents the risks related to the relation of subcontracting and the importance of the modes of management of these risks in the performance of the relation of subcontracting, the comprehension and the determination of interaction enter the subcontractor and the customer; they lead the subcontractors particularly to search or create relational values able to maintain, to sustain the relation and to avoid all risks of opportunism and uncertainty of the customers. And thus we supposed that the proximity will play a significant role in the search and the creation of relational values. We put our attention on automobile subcontracting since recently the development of the subcontracting of proximity in automobile industry in Morocco becomes the concern first with the needs for the companies of the sector (Moroccan association of industry and the automobile Trade, 2014).